Fibrin polymer on the surface of biomaterial implants drives the foreign body reaction. (October 2021) - Balabiyev, Arnat; Podolnikova, Nataly P.; Kilbourne, Jacquelyn A.; Baluch, D. Page; Lowry, David; Zare, Azadeh; Ros, Robert; Flick, Matthew J.; Ugarova, Tatiana P.
Abstract: Implantation of biomaterials and medical devices in the body triggers the foreign body reaction (FBR) which is characterized by macrophage fusion at the implant surface leading to the formation of foreign body giant cells and the development of the fibrous capsule enveloping the implant. While adhesion of macrophages to the surface is an essential step in macrophage fusion and implanted biomaterials are known to rapidly acquire a layer of host proteins, a biological substrate that is responsible for this process in vivo is unknown. Here we show that mice with genetically imposed fibrinogen deficiency display a dramatic reduction of macrophage fusion on biomaterials implanted intraperitoneally and subcutaneously and are protected from the formation of the fibrin-containing fibrous capsule. Furthermore, macrophage fusion on biomaterials implanted in Fib AEK mice that express a mutated form of fibrinogen incapable of thrombin-mediated polymerization was strongly reduced. Despite the lack of fibrin, the capsule was formed in Fib AEK mice, although it had a different composition and distinct mechanical properties than that in wild-type mice. Specifically, while mononuclear α-SMA-expressing macrophages embedded in the capsule of both strains of mice secreted collagen, the amount of collagen and its density in the tissue of Fib AEK mice was reduced. These data identify fibrin polymer as a key biological substrate driving the development of the FBR.